Al-Hakim al-Naisaburi dan al-Tirmidzi: (Studi Perbandingan Manhaj) - Husain, Ahmadi (STAIN Majene, 2023)
This paper presents the results of a research comparing the methodologies of al-Haki>m al-Naisa>buri> and al-Tirmi>dzi>. The research was conducted using a literature review method. The findings in the study revealed differences between al-Haki>m and al-Tirmi>dzi> in determining the criteria for rija>l. Al-Haki>m, in establishing the criteria for the righteousness of narrators, employs three standards of righteousness: Islam, avoidance of innovation (bidah), and abstaining from sinful acts. On the other hand, al-Tirmi>dzi> utilizes five standards of righteousness, including safeguarding one's honor (muruat), refraining from major sins, avoiding minor sins, abstaining from innovation, and refraining from sinful behavior. The use of these criteria has implications for the narration of hadiths by both scholars. Al-Tirmi>dzi>, when narrating a hadith that is considered weak (daif) by previous scholars, but its weakness does not render its application prohibited, then al-Tirmi>dzi> considers such a hadith as hasan. In contrast, al-Haki>m, in his assessment, categorizes hadiths that are considered hasan by other scholars into the category of sahih. This approach has led to criticism of al-Haki>m by other scholars.